Mechanism of Congenital Chagas Disease: Effective Infection Depends on the Interplay Between Trypanosoma cruzi and the Different Tissue Compartments in the Chorionic Villi of the Human Placenta - Duaso, Juan; Castillo, Christian; Kemmerling, Ulrike (IntechOpen, 2012)
None